2007
DOI: 10.1890/06-0031.1
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Regulation of Nitrogen Export From Urban Catchments: Interactions of Storms and Landscapes

Abstract: In urban catchments of arid central Arizona, we investigate how the export of mineral and organic nitrogen (N) in storm runoff is regulated by interactions between local landscape characteristics and broader scale storm features. First, we test whether N export is more a function of (1) processes that affect N concentration in runoff or (2) the propensity of the catchment to convey rainfall as runoff. With data pooled across catchments, the mass of N in export (load) is determined by processes regulating runof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 38 publications
1
49
1
1
Order By: Relevance
“…Larger watersheds also had lower runoff coefficients and therefore retained more DIN, as noted by Lewis and Grimm. 43 Sources of NO 3 − in Urban Stormwater. The isotopic composition of NO 3 − varied significantly across rainfall, soil, and impervious surfaces (Figure 3 − in rainfall were significantly higher than both impervious surface and soil sources (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Larger watersheds also had lower runoff coefficients and therefore retained more DIN, as noted by Lewis and Grimm. 43 Sources of NO 3 − in Urban Stormwater. The isotopic composition of NO 3 − varied significantly across rainfall, soil, and impervious surfaces (Figure 3 − in rainfall were significantly higher than both impervious surface and soil sources (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Given that the Sonoran desert is nitrogen limited (Westerman and Tucker, 1978;Whitford, 2002), we expected to observe nitrogen retention at LD and therefore low NO 3 and NO 2 runoff concentrations. However, this was not the case and the literature supports a two part explanation for the high NO 3 concentrations across sites, which can be extended to all R2 constituents: (1) solutes deposited during dry conditions accumulated within the catchment due to soil water limitations for biogeochemical activity, resulting in mobilization of accumulated solutes during rainfall and subsequent runoff (Lewis and Grimm, 2007;McCrackin et al, 2008) and (2) biogeochemical processes such as mineralization, nitrification and phosphorous retention increase in response to soil wetting, leading to accumulation of solutes in the soil between storm events and which are flushed during subsequent runoff (Austin et al, 2004;Welter et al, 2005). Both of these processes are likely to occur in the uplands and ephemeral stream channels.…”
Section: Runoff Quality Responsesmentioning
confidence: 94%
“…Some conceptual models suggest that both, urban runoff quantity and quality, are primarily controlled by percent impervious cover (Arnold and Gibbons, 1996;Paul and Meyer, 2001;Schueler, 1994), while others indicate that urban runoff quality and quantity are largely controlled by the extent of catchment connectivity and the characteristics of the stormwater drainage system (Carle et al, 2005;Hatt et al, 2004;Meierdiercks et al, 2010;Ogden et al, 2011;Walsh et al, 2009). However, few studies have specifically addressed how urbanization alters runoff responses in semi-arid regions (for example: Asaf et al, 2004;Ishaq and Alassar, 1999;Jiries et al, 2001;Lewis and Grimm, 2007) where runoff and subsequent streamflow occur only in response to rainfall. A recent study by Gallo et al (2012), for example, showed that short term (hours) partitioning of rainfall controls the temporal patterns of urban hydrologic responses in semi-arid study catchments in Tucson, AZ.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, legacy-sediment-rich fill terraces have been shown to dampen N removal pathways in the long-buried relict soils which they overlie, while also acting as potential sources of nitrate (NO − 3 ) to waterways (Weitzman et al, 2014). Climate-driven export of N from watersheds is known to occur (Howarth et al, 2006;Lewis and Grimm, 2007;Kaushal et al, 2008aKaushal et al, , 2010Duncan et al, 2015), with N stored during "dry" years or seasons and flushed from watersheds during "wet" years or seasons. Such drying-rewetting cycles have been linked to regionwide pulses of high NO − 3 concentrations in tributaries of the Chesapeake Bay .…”
Section: Introductionmentioning
confidence: 99%